Pengaruh Faktor-Faktor Perilaku Konsumen terhadap Keputusan Pembelian Produk Frozen Food di Adam Frozen Food Kabupaten Bekasi - Hadiansah, Rini; Azzahra , Fatimah; Budiandrian, Bayu (Paspalum: Jurnal Ilmiah Pertanian, 2024)
Bekasi Regency is one of the metropolitan areas in Indonesia with rapid population and urban growth. The majority of Bekasi Regency residents have a busy lifestyle with a busy work routine. This time limitation makes Bekasi Regency residents need practical food products such as frozen food. Frozen food products are the right choice because they are easy to store, durable, and quick to serve. One of the frozen food stores in Bekasi Regency is Adam Frozen Food, which sells frozen food products as a solution to meet food needs without spending excessive time and energy. Competition in the frozen food industry is getting tighter with many offering similar products with competitive quality and prices. With this condition, research is needed to understand the factors of consumer behavior in purchasing frozen food products at Adam Frozen Food, Bekasi Regency. The purpose of this research is to analyze the influence of cultural factors, social factors, personal factors and psychological factors on purchasing decisions for frozen food products at Adam Frozen Food. The sampling method used the Lemeshow formula with 100 respondents. The data analysis used is multiple linear regression. The results showed that cultural factors, social factors, personal factors and psychological factors simultaneously influenced the variable purchasing decisions for frozen food products at Adam Frozen Food. Social factors, personal factors and psychological factors partially influence the decision to purchase frozen food products at Adam Frozen Food. Meanwhile, cultural factors partially have no effect on purchasing decisions for frozen food products at Adam Frozen Food.